Production of Functional Yogurt Drink, Apple and Orange Juice Using Nano-Encapsulated L. brevis Within Sodium Alginate-Based Biopolymers - Mohaisen, Mohammed Jawad M.; Yildirim, Rusen Metin; Yilmaz, Mustafa Tahsin; Durak, Muhammed Zeki (AMER SCIENTIFIC PUBLISHERS, 2019)
The study objective was to improve functional properties of yogurt drink, apple and orange which were produced by addition of free and encapsulated probiotics. For this purpose, probiotic L. brevis E25 bacterial cells were encapsulated in sodium alginate by electrospinning method. In this study, Fourier-transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), XRD, and Nuclear Magnetic Resonance (NMR) techniques were used to characterize the L. brevis encapsulated with nanofiber. The free and nano-encapsulated probiotic bacteria were inoculated into ayran, apple and orange juice, where bacterial viability, pH, brix and color were assessed each 3 days for the ayran and each week for the apple and orange juice for six-week period. The encapsulated probiotic organisms showed an important survival ratio in the three products comparing to the free probiotic bacteria, where the pH and the brix showed no decreasing leading to conclude that the nanoen-capsulation of probiotic L. brevis cell using the electrospinning method lead to functional yet more stable food and have the potential of increased benefits.
Keywords: Nanoencapsulation; Probiotic; L. brevis; Electrospinning; Ayran; Fruit Juice; MICROENCAPSULATION; SURVIVAL; Science & Technology - Other Topics; Materials Science; Physics